Genetic, antigenic, and pathogenic characteristics of Newcastle disease viruses isolated from geese in China. (July 2017) - Xu, Qianqian; Sun, Junfeng; Gao, Mengying; Zhao, Shasha; Liu, Huairan; Zhang, TingTing; Han, Zongxi; Kong, Xiangang; Liu, Shengwang
Four Newcastle disease virus (NDV) strains were isolated from domestic, commercial geese that showed clinical signs that were believed to be the result of NDV infections. The genetic, antigenic, and pathogenic characteristics of the 4 NDVs were compared with those of NDV strains that were isolated from chickens. The complete genomes of 2 of the NDV strains contained 15, 186 nucleotides (nt); the other 2 contained 15, 192 nt, and exhibited the typical genomic organization of genotype II NDV and molecular characteristics of VIId NDVs. Phylogenetic analysis confirmed that the genotype II and VIId NDVs that were isolated from geese belonged to the same clusters as the corresponding genotypes of the chicken isolates. A serologic assay demonstrated that the antigenic relatedness among the NDVs was associated with their genotypes, rather than their hosts, and that amino acid substitutions in the F and/or HN proteins may contribute to the antigenic differences among these NDV genotypes. Geese infected with genotype VIId NDVs that were isolated from geese and chickens showed similar pathologic characteristics. NDVs that were isolated from geese did not differ in genetic, serologic, and pathogenic characteristics from those isolated from chickens, indicating that these NDVs were derived from chicken NDVs. Given the significance of geese in NDV epidemiology, effective biosecurity measures should be adopted to prevent the interspecies transmission of NDVs.